THE USE OF MODELED WRITING STRATEGY ON STUDENTS’ NARRATIVE TEXT ABILITY AT GRADE VIII SMP SWASTA PTPN IV BAH JAMBI IN ACADEMIC YEAR 2019/2020 - Marhaeni Matondang; Devi Sundari Samosir (Program Studi Pendidikan Bahasa Inggris FKIP, 2021)
This study aims to find out whether the writing modeling strategy improves the ability to write narrative texts for seventh grade students of PTPN IV Bah Jambi T.P. Private Junior High School. 2019/2020. There are several reference sources used in writing this research journal as well as conducting direct research on seventh grade students of PTPN IV Bah Jambi Private Junior High School T.P. 2019/2020. Based on the results of data analysis, it was found that the writing modeling strategy significantly improved the ability to write narrative texts for the seventh grade students of PTPN IV Bah Jambi T.P. Private Junior High School. 2019/2020